Oxygen-Deficient Stannic Oxide/Graphene for Ultrahigh-Performance Supercapacitors and Gas Sensors - Lin, Liyang (Nanomaterials (Basel), 2021)
The metal oxides/graphene nanocomposites have great application prospects in the fields of electrochemical energy storage and gas sensing detection. However, rational synthesis of such materials with good conductivity and electrochemical activity is the topical challenge for high-performance devices. Here, SnO(2)/graphene nanocomposite is taken as a typical example and develops a universal synthesis method that overcome these challenges and prepares the oxygen-deficient SnO(2) hollow nanospheres/graphene (r-SnO(2)/GN) nanocomposite with excellent performance for supercapacitors and gas sensors. The electrode r-SnO(2)/GN exhibits specific capacitance of 947.4 F g(−1) at a current density of 2 mA cm(−2) and of 640.0 F g(−1) even at 20 mA cm(−2), showing remarkable rate capability. For gas-sensing application, the sensor r-SnO(2)/GN showed good sensitivity (~13.8 under 500 ppm) and short response/recovering time toward methane gas. These performance features make r-SnO(2)/GN nanocomposite a promising candidate for high-performance energy storage devices and gas sensors.